Dieta rica em frutose piora a variabilidade da frequência cardíaca e estresse oxidativo no infarto agudo do miocárdio experimental - Lirio, Layla Mendonça (2021)
The change in the population's dietary pattern in recent years, opting for the consumption of industrialized products and the food industry school for sweetening products with fructose, seems to be related to the increase in cases of metabolic alterations in the population. In addition, some of the metabolic changes are risk factors, as well as inadequate nutrition, for the development of cardiovascular diseases and the occurrence of acute events, such as myocardial infarction. Our hypothesis, therefore, is that high fructose consumption for a long period of time in normotensive animals interferes with hemodynamic and metabolic parameters and in the production of reactive oxygen species after myocardial infarction. Methods: Wistar rats aged 6 weeks were treated with water or fructose (10%) for 7 weeks, in the seventh week, ligation of the left anterior descending coronary artery was introduced, the treatment with fructose suspended and followed for seven days. Capillary blood glucose was assessed weekly and at the end of the protocol, glucose tolerance and insulin sensitivity tests were performed in the seventh week and not the seventh day after the infarction. Catheterization of the femoral artery was performed for invasive assessment of blood pressure and heart rate, and of the carotid artery for assessment of hemodynamic parameters of the left ventricle, both performed on the seventh day after the infarction. Lean mass, abdominal fat and visceral weight were measured. And the animals' blood was collected for biochemical analysis and evaluation of the production of reactive oxygen species. Results: glycemia was shown to be increased in animals that consume the fructose diet, these animals also added greater insulin resistance and lower glucose tolerance, worsening after 7 days of infarction. An increase in left ventricular systolic pressure and a reduction in heart rate variability were obtained in the fructose-treated group. There was an increase in serum triglyceride levels and in the production of reactive oxygen species in this same group. Conclusions: We demonstrate that a high fructose diet promotes changes in triglyceride levels, insulin sensitivity, glucose tolerance, increased left ventricular pressure after myocardial infarction, reduced heart rate variability and increased production of reactive species of oxygen. Suggesting that a diet rich in fructose worsens cardiac muscle adaptation to myocardial infarction.